PERBANDINGAN PENGISIAN JABATAN HAKIM ANTARA INDONESIA DENGAN JEPANG - Haris Kurnia Anjasmana (Muhammadiyah University Press, 2019)
To produce judges with integrity, professionalism and legal mastery, of course the initial steps are determined by how the judicial filling mechanism is filled. The mechanism for filling judges in Indonesia is experiencing problems because it is not regulated in the judicial power law, only regulated through a Supreme Court Regulation. Plus the still unclear institution that has the authority to do the selection of judges. Japan itself has a procedure to fill a judge's office which is considered one of the best, where the selection can be done through a special school of judges, or a state exam. So it's interesting to compare the filling positions between Indonesia and Japan. Which become the orderly compationis is which institution has the authority to conduct a selection of judges, how about the mechanism to fill a judge's office, as for what identifies the problem in this paper is whether the institution authorized to conduct the selection of first-level judges in Indonesia and Japan is credible or not? second: to what extent are the mechanisms for filling judges in Indonesia and Japan able to produce qualified and integrity judges? Keywords: Filling, recruitment, judge, quality, Japan